1984
DOI: 10.1017/s000335610004160x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Canadian Holstein × British Friesian and British Friesian steers for beef production. 2. Carcass characteristics

Abstract: A comparison was undertaken of 85 Holstein x Friesian (HF) and 84 Friesian (F) steer carcasses that had been produced on three production systems. These were: intensive barley beef (BB); grass/cereal 18 month; and 24 month forage system. On each system, HF steers were heavier at slaughter (over all systems,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…The lower kill-out proportion of HO in the present study is likely due to a higher proportion of gastrointestinal tract . The superior carcass conformation class of FR over HO is in agreement with the findings of Baber et al (1984), Kempster et al (1988) and McGee et al (2005), but at variance with the observations of Keane and More O'Ferrall (1988). The animals used in the study of McGee et al (2005) were genetically similar to those used in the present study, whereas Keane and More O'Ferrall (1988) compared Friesians with Holstein × (Holstein × Friesians).…”
Section: Slaughter and Carcass Traitssupporting
confidence: 90%
See 1 more Smart Citation
“…The lower kill-out proportion of HO in the present study is likely due to a higher proportion of gastrointestinal tract . The superior carcass conformation class of FR over HO is in agreement with the findings of Baber et al (1984), Kempster et al (1988) and McGee et al (2005), but at variance with the observations of Keane and More O'Ferrall (1988). The animals used in the study of McGee et al (2005) were genetically similar to those used in the present study, whereas Keane and More O'Ferrall (1988) compared Friesians with Holstein × (Holstein × Friesians).…”
Section: Slaughter and Carcass Traitssupporting
confidence: 90%
“…The superior kill-out proportion and conformation class of the beef breeds over the dairy breeds is widely acknowledged in the literature (Keane, 1994(Keane, , 2003Steen and Kilpatrick, 1995;Keane and Drennan, 2008). A higher kill-out proportion for FR over HO has been observed in some studies (Cook and Newton, 1979;Baber et al, 1984;McGee et al, 2005) but not in others (Flanagan, 1982;Keane and More O'Ferrall, 1988;Kempster et al, 1988). This inconsistency is probably due to the variability in dairy genetic merit of the FR and HO animals used in the different studies.…”
Section: Slaughter and Carcass Traitsmentioning
confidence: 99%
“…There were no genetic group ×S interactions. retroperitoneal fat in BB compared to AA and the dairy strains, is in agreement with the findings of Keane and Drennan (2008), but the greater weight and proportion of perinephric plus retroperitoneal fat in FR compared to HO has not been observed previously (Cook and Newton, 1979;Baber et al, 1984;Keane and More O'Ferrall, 1988;McGee et al, 2005). However, Keane (2003) reported that Friesians of New Zealand origin did have a greater weight and proportion of perinephric plus retroperitoneal fat than Holstein-Friesians of European/North American descent.…”
Section: Slaughter Carcass and Non-carcass Traitssupporting
confidence: 83%
“…Some information on the differences in carcass composition between British Friesians and Canadian Holsteins has been obtained from British studies (Cook and Newton, 1979;Tas and Scott, 1982;Baber, Rowlinson, Willis and Chalmers, 1984) but the numbers of carcasses evaluated have been relatively small and the studies have not involved an overall evaluation of the efficiency of lean gain.…”
Section: Introductionmentioning
confidence: 99%